Soil-Available Nitrogen and Phosphorus and Their Temporal Stability in the Tibetan Grasslands - Guangyu Zhang; Rang Ding; Wei Sun; Gang Fu (Agronomy)
Uncertainties regarding the responses of soil-available nitrogen and phosphorus (i.e., ammonium nitrogen, NH4+–N; nitrate nitrogen, NO3−–N; available phosphorus, AP) to global changes pose significant challenges to predicting future shifts in plant productivity and livestock development in alpine ecosystems, where these nutrients are critical limiting factors. This study aimed to (1) compare the relative contributions of climate warming, precipitation change, and radiation change on soil-available nitrogen and phosphorus; (2) reveal the decoupling relationships between nutrient contents and their temporal stability; and (3) compare the sensitivity of nutrient contents and their temporal stability. We conducted a regional-scale analysis on soil profiles of 0–10 and 10–20 cm through random forest models across alpine grasslands on the Tibetan Plateau (2000–2020), integrating climate datasets (temperature, precipitation, and radiation) and a normalized difference vegetation index. Temporal stability indicated the reciprocal of the coefficient of variation. Trend analyses were used to quantify the change rate of the nutrient contents and their temporal stability. Three key findings emerged. First, radiation change can exert stronger effects on soil-available nitrogen and phosphorus for some cases. Second, both the contents and temporal stability of NH4+–N, NO3−–N, and AP increased in 13.62–25.80% of grasslands but decreased in 18.74–41.80%. Additionally, 18.71–52.03% of areas showed nutrient increases coupled with decreased temporal stability (while being vice versa in 10.28–26.29%). Third, the relative change in temporal stability exhibited greater ranges (−3081.02% to 3852.73%) than those of the nutrient contents (−355.95% to 947.56%). Therefore, radiation change should be valued in regulating the variations in soil NH4+–N, NO3−–N, and AP. The changes in the contents of NH4+–N, NO3−–N, and AP were not always in sync with the changes in their temporal stability. Stability metrics may better reflect ecosystem vulnerability to global change. All these findings underscore the importance of radiation changes and concurrently considering soil-available nitrogen and phosphorus contents and their temporal stability.